Enhancing the Curie Temperature of Ferromagnetic Semiconductor (Ga,Mn)As to 200 K via Nanostructure Engineering - Chen, Lin; Yang, Xiang; Yang, Fuhua; Zhao, Jianhua; Misuraca, Jennifer; Xiong, Peng; von Molnár, Stephan (Nano letters, 2011)
We demonstrate by magneto-transport measurements that a Curie temperature as high as 200 K can be obtained in nanostructures of (Ga,Mn)As. Heavily Mn-doped (Ga,Mn)As films were patterned into nanowires and then subject to low-temperature annealing. Resistance and Hall effect measurements demonstrated a consistent increase of T C with decreasing wire width down to about 300 nm. This observation is attributed primarily to the increase of the free surface in the narrower wires, which allows the Mn interstitials to diffuse out at the sidewalls, thus enhancing the efficiency of annealing. These results may provide useful information on optimal structures for (Ga,Mn)As-based nanospintronic devices operational at relatively high temperatures.